Exile and Home in the Novels of some Contemporary Anglophone Arab writers: Ibrahim Fawal, Shaw Dallal, Yasmin Zahran and Nada Awar Jarrar - HANDOUR MOHAMED (Faculté des Lettres et Sciences Humaines, Béni Mellal - Doctorat ou Doctorat National, 2019)
Though the corpus is apparently heterogeneous and variegated, it is unified by the plight of displacement that engenders a coercive break with the terre natale. The Palestinian Anglophone authors Ibrahim Fawal, Shaw Dallal and Yasmine Zahrane share their main concerns with their Lebanese counterpart, Nada Awar Jarrar. Obliquely or directly, there is an aura of exilic life resonating in the five novels and the characters’ tendency to write themselves as they attempt to vitiate the traumatizing effect of this coercive parting with what can be tendentiously dubbed “the homeland.” The home /exile dyad acquires significance within specific historical, political and cultural contexts. That’s why the conditions that produce the Palestinian exile are dissimilar to those that drive the Lebanese characters outside their home. After all, the Isreali colonial occupation of the Palestinian land and the catastrophic aftermath of the infamous exodus cannot be compared to the Lebanese Civil War and its resultant border crossings. In spite of this difference, this thesis is built on the common and salient denominator of the intricacies inherent in the dichotomy of home and exile and the mutability of a people’s identity in the course of the excessive mobility that marks their lives in exile. This mutability, however, does not deprive the characters from exulting in the myth of an eternal return. To address the intricacies of exile and home, a multi-disciplinary approach is adopted with a special focus on the materiality of the text. That is the narratives under study are not mere works of fiction but also products of given historical, political and cultural circumstances. In this regard the text is laced with living experiences as it is not antiseptically quarantined from external realities.
Keywords: Exile; home; space; Zionism; return; hegemony; ambivalence; displacement; the catastrophe; identity; the exodus.; Littérature; Études Postcoloniales